EXPLORING AN INTEGRATED MULTI-LEVEL COLLABORATIVE EVALUATION MODEL FOR PRIMARY STUDENTS: THE CASE OF CHONGQING YUDAISHAN PRIMARY SCHOOL - Hong, Zou (วารสารพุทธปรัชญาวิวัฒน์, 2023)
The objectives of this research article were to resolve problems resulting from an education system where score is the only evaluation criterion in Chinese primary and secondary schools, we have constructed an integrated multi-level collaborative student evaluation model at Yudaishan Primary School in Jiangbei District, Chongqing, China through seven years of exploration. Based on this model, we evaluate students through a free combination of multi-situations, multi-cooperation, and multi-methods according to the needs of students’ academic evaluation and students’ comprehensive quality evaluation. The multiple combination evaluation breaks through the traditional Chinese student evaluation model of “score only”, and provides a reference path for the reform of student evaluation in primary and secondary schools.    The results of this research show that in the process of academic evaluation or comprehensive quality evaluation of students, the implementation of the integrated multi-level collaborative student evaluation model will benefit students’ physical and mental health, teachers’ “teaching” and students’ “learning”. In specific, the model emphasizes that student evaluation should be conducted in multiple life situations, achieved through the coordination of multiple subjects and realized via an integrated use of multiple methods. The overall development of students can be greatly guaranteed, and the research goal of improving the “score-based” student evaluation model can be achieved.